Selection of perching site background color by Hamadryas feronia (Lepidoptera: Nymphalidae) in Costa Rica: Implications for industrial melanism - Murillo-Hiller, Luis Ricardo (2012)
Observations of the increased frequency of melanic forms in moths of the genus Biston in Great Britain after the industrial revolution lead to the development of the theory of Industrial Melanism. Nonetheless, arguments against that interpretation of the experimental evidence have polarized acceptance of the concept. New evidence based on diurnal butterflies is more credible because it involves behavior that can be seen in action, during daylight, and because the natural history of the selected species is well known. An experiment was carried out in which three substrate colors (white, black, and gray) were employed to test the landing preferences of Hamadryas feronia. A marked preference was observed for landing on white and gray, and a chi-square (N=644 tests) showed evidence of a preference by males to land on white, and for females to land on gray. Black was rejected perhaps because it provides very little background matching with the butterfly’s colors. The butterfly habit of perching selectively on particular color substrates is a genetically fixed behavior, where the males possibly choose white as a tactic to be noticed by females and attract them, whereas females prefer gray to enhance crypsis and avoid attracting predators.